2000
DOI: 10.1097/00006534-200010000-00022
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Treatment of Brachial Plexus Injuries in Adults

Abstract: Posttraumatic brachial plexus palsy is a severe injury primarily affecting young individuals at the prime of their life. The devastating neurological dysfunction inflicted in those patients is usually lifelong and creates significant socioeconomic issues. During the past 30 years, the surgical repair of these injuries has become increasingly feasible. At many centers around the world, leading surgeons have introduced new microsurgical techniques and reported a variety of different philosophies for the reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 82 publications
1
75
0
6
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Many options exist for the restoration of elbow flexion and the most appropriate option depends largely on the availability of donor motor nerves. 10,11 In 1994 Oberlin et al 12 described the transfer of an expendable flexor carpi ulnaris (FCU) fascicle from the ulnar nerve directly to the biceps branch of the musculocutaneous nerve to reconstruct elbow flexion. In a follow-up series 13 of 32 patients reported in 2004 elbow flexion of Medical Research Council (MRC) grades 3 to 4 was achieved in 94% of cases and no significant donor morbidity was seen.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Many options exist for the restoration of elbow flexion and the most appropriate option depends largely on the availability of donor motor nerves. 10,11 In 1994 Oberlin et al 12 described the transfer of an expendable flexor carpi ulnaris (FCU) fascicle from the ulnar nerve directly to the biceps branch of the musculocutaneous nerve to reconstruct elbow flexion. In a follow-up series 13 of 32 patients reported in 2004 elbow flexion of Medical Research Council (MRC) grades 3 to 4 was achieved in 94% of cases and no significant donor morbidity was seen.…”
mentioning
confidence: 99%
“…3 Studies worldwide clearly have shown that clinical examination alone has several limitations. 1,3 For example, patients with upper-root avulsion develop a trick movement for the action of rhomboids. The middle fibers of the trapezius act with rhomboids to produce retraction of the scapula.…”
Section: Discussionmentioning
confidence: 99%
“…EMG study of these muscles (paraspinal EMG) helps one to differentiate intraforaminal and extraforaminal brachial plexus lesions. 1,2 The aim of the present study was to assess the efficiency individually and in combination with 3 investigative tools namely-clinical examination, routine EMG, and paraspinal EMG in preoperative differentiation of extraforaminal and intraforaminal lesions and to correlate these with the peroperative findings.…”
mentioning
confidence: 99%
“…Für die Langzeitprognose der Extremitätenfunktion ist der Grad und die Rekonstruktion der Nervenverletzung [39,41] die entscheidende Determinante und bedarf hinsichtlich der Indikation, des Timings und des zu erwartenden Outcomes mehr noch als die Gefäß-und Knochenrekonstruktion ein multidisziplinäres Behandlungskonzept unter Hinzuziehung von mikro-/hand-und neurochirurgischen Spezialdisziplinen [2,32,34]. Primäre End-zu-End epineurale Naht mit 9-0 oder 10-0 liefert dabei die besten Resultate,vorausgesetzt es liegt keine signifikante Spannung an der Anastomose vor.…”
Section: Neben Einem Abriss Der Aaxillaris Fand Sich Eine Sternoklavunclassified